2019
DOI: 10.1111/jocn.14729
|View full text |Cite
|
Sign up to set email alerts
|

The experience of person‐centred practice in a 100% single‐room environment in acute care settings—A narrative literature review

Abstract: Aims and objectives To review published research into the staff and adult patient experience of person‐centred practice in a 100% single‐room environment in acute care. Background There has been a significant move towards the 100% single‐room environment within healthcare systems. Furthermore, there has been a global move for developing person‐centred practice in a range of healthcare settings. Some studies have linked the role of the physical environment to patient outcomes and improved patient satisfaction; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
(135 reference statements)
0
4
0
Order By: Relevance
“…There were no significant differences in cognitive development, length of admission, growth, complications of ICU admission and mortality. Four other systematic reviews3 40 154 155 and two scoping reviews39 156 assessed outcomes in a more general hospital population and generally found mixed evidence of benefits from single rooms, with each review identifying between 12 and 44 studies that reported advantages, disadvantages and neutral findings for most clinical outcomes, but a more positive result for patient privacy and satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…There were no significant differences in cognitive development, length of admission, growth, complications of ICU admission and mortality. Four other systematic reviews3 40 154 155 and two scoping reviews39 156 assessed outcomes in a more general hospital population and generally found mixed evidence of benefits from single rooms, with each review identifying between 12 and 44 studies that reported advantages, disadvantages and neutral findings for most clinical outcomes, but a more positive result for patient privacy and satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…A literature review by Kelly et al, (2019) found that key elements such as communication, authentic engagement and the physical environment were recognised as important. This review also found that while there was increasing evidence of the impact of culture and care processes on patient and staff experience, generally the relationship between the experiences of the two groups was not explored.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…The interviews were audiorecorded and lasted on average 30 minutes. An interview guide (Figure 4) was created based on the findings of a literature review (Kelly et al, 2019) and on person-centred outcomes from the Person-centred Practice Framework (McCormack & McCance, 2017). Questions were open-ended with prompts where required.…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation